The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/ijgi8120586
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Cell Neighborhood Size in Landscape Metrics Evaluation and Free or Open Source Software Implementations

Abstract: Landscape metrics constitute one of the main tools for the study of the changes of the landscape and of the ecological structure of a region. The most popular software for landscape metrics evaluation is FRAGSTATS, which is free to use but does not have free or open source software (FOSS). Therefore, FOSS implementations, such as QGIS's LecoS plugin and GRASS' r.li modules suite, were developed. While metrics are defined in the same way, the "cell neighborhood" parameter, specifying the configuration of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Division index yields the probability that two randomly selected cells are not located in the same patch. Mean Euclidean nearest‐neighbour distance accounts for the number of highly isolated patches, whereas aggregation index evaluates the frequency with which patch pairs occur side‐by‐side in the landscape (McGarigal et al 2012, Zatelli et al 2019). We selected these metrics as they can be successfully used to compare fragmentation among different landscapes and, in our case, different time bins (He et al 2000, Cornejo‐Denman et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Division index yields the probability that two randomly selected cells are not located in the same patch. Mean Euclidean nearest‐neighbour distance accounts for the number of highly isolated patches, whereas aggregation index evaluates the frequency with which patch pairs occur side‐by‐side in the landscape (McGarigal et al 2012, Zatelli et al 2019). We selected these metrics as they can be successfully used to compare fragmentation among different landscapes and, in our case, different time bins (He et al 2000, Cornejo‐Denman et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the assessment of the landscape metrics was applied to obtain landscape statistics [13]. Subsequently, landscape metrics were calculated in relation to the raster layer [14].…”
Section: Methodsmentioning
confidence: 99%
“…The oldest imagery set belongs to the "Volo GAI" (Gruppo Areonautico Italiano, Italian Aeronautical Group) of 1954. The aereal images are available as 23 × 23 cm prints and have been digitized at 600dpi after tests have shown that higher resolutions do not carry any significative advantage (Gobbi et al, 2019a).…”
Section: Orthophotosmentioning
confidence: 99%
“…The flight covers the whole Italy and the ortho-rectified images were not available for the Trentino region, but for a few small areas. Therefore a set of 130 B/W images, with mean scale of 1:35,000 and ground resolution of 2m, have been ortho-rectified in the Italian national Rome40 datum using GRASS GIS (Gobbi et al, 2019a…”
Section: Orthophotosmentioning
confidence: 99%